2017
DOI: 10.1038/s41598-017-13785-3
|View full text |Cite
|
Sign up to set email alerts
|

IP-10 Kinetics in the First Week of Therapy are Strongly Associated with Bacteriological Confirmation of Tuberculosis Diagnosis in HIV-Infected Patients

Abstract: Simple effective tools to monitor the long treatment of tuberculosis (TB) are lacking. Easily measured host derived biomarkers have been identified but need to be validated in larger studies and different population groups. Here we investigate the early response in IP-10 levels (between day 0 and day 7 of TB therapy) to identify bacteriological status at diagnosis among 127 HIV-infected patients starting TB treatment. All participants were then classified as responding or not responding to treatment blindly us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 31 publications
(43 reference statements)
4
13
1
Order By: Relevance
“…However, this study also detected urine IP-10 levels after 2 months of an intensive anti-TB drug therapy, which is the point when clinicians routinely use radiological and bacteriological tests to determine treatment progress. Although recent studies have reported a decline in blood IP-10 levels after 2 weeks of efficient anti-TB drug therapy as an early biomarker for treatment response [ 21 , 22 ], this study demonstrated a peak in urine IP-10 levels after 2 months of treatment in HIV-negative patients with tuberculosis. Moreover, the same trend was observed in patients regardless of risk factors for TB relapse or treatment failure.…”
Section: Discussioncontrasting
confidence: 53%
“…However, this study also detected urine IP-10 levels after 2 months of an intensive anti-TB drug therapy, which is the point when clinicians routinely use radiological and bacteriological tests to determine treatment progress. Although recent studies have reported a decline in blood IP-10 levels after 2 weeks of efficient anti-TB drug therapy as an early biomarker for treatment response [ 21 , 22 ], this study demonstrated a peak in urine IP-10 levels after 2 months of treatment in HIV-negative patients with tuberculosis. Moreover, the same trend was observed in patients regardless of risk factors for TB relapse or treatment failure.…”
Section: Discussioncontrasting
confidence: 53%
“…Furthermore, the identification of new additional post-translational modifications of IP-10 and their role in TB pathogenesis may also be explored. Importantly, the "end therapy" time point differs between active TB and pneumonia patients (6 months vs 1 month), however, different drug regimens are expected for these diseases; shorter time courses during therapy, as previously described (Garcia-Basteiro et al, 2017), will better highlight the differences of IP-10 and its agonist/antagonist levels in urine.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, additional tests and new biomarkers for predicting treatment efficacy are needed. Blood IP-10 has been demonstrated as an early predictor of treatment response as its levels rapidly decrease in the first week of treatment, mainly in microbiologically confirmed active TB with or without HIV infection (Garcia-Basteiro et al, 2017;den Hertog et al, 2015;Chung et al, 2016). In this study we found declining levels of total and agonist/antagonist IP-10 forms in urine of patients with active TB during specific therapy but not in patients with pneumonia, suggesting that modifications of IP-10 forms during therapy may be associated to TB disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been demonstrated that IP-10 secretion during TB disease originates from infected macrophages and multinucleated giant cells located in the granulomas, and early inactivation of the secreted chemokine by antagonist form of IP-10 which binds to CXCR3 but does not induce signalling, may also play a role in the pathogenesis of TB 51,52 . Several studies show that IP-10 declines during efficient treatment of many diseases including TB 25,38,42,53,54 . Limited data also indicates that IP-10 increases in non-cured TB patients from baseline to 2 months of treatment, and in TB patients who relapse or develop active TB disease 25,55 .…”
Section: Discussionmentioning
confidence: 99%